Indentifying farmers’ preferences and constraints to maize production in two agro‑ecological zones in Burkina Faso - Dao, Abdalla; Sanou, Jacob; Gracen, Vernon; Danquah, Eric Y. (BioMed Central, 2015)
Background: The low adoption of technologies, developed by research institutions, by farmers substantiates the need for client orientation in research and development. Hence, to bridge the gap between breeders and farmers and to ensure that new varieties fit farmers’ preferences and suit their socioeconomic situations, Participatory Rural Appraisals (PRA) were undertaken in two agro-ecological zones (North-Sudan and South-Sudan) to determine maize varieties farmers grow, farmers’ preferences in choice of the varieties and to evaluate farmers’ perceptions of constraints to maize production. Results: Farmers grow both local and improved varieties to meet their multiple objectives in maize farming. Nearly 63 % of the farmers grow local maize varieties whilst about 37 % grow improved varieties. All the different varieties are grown in both northern and southern zones but, in general, early maturing maize varieties are grown in northern zones while late maturing maize varieties are planted in southern zones. This study revealed that farmers preferred varieties that carry traits like high yield potential, early maturity, tolerance to drought, Striga and low soil fertility in all districts. Maize production in the two zones is constrained by a variety of related factors, the extent of contribution of each factor varies across the districts. The main constraints to maize production are poor cash flow, inadequate farm tools, poor extension service, drought and pests. Striga is considered as the most important pest followed by termites. Conclusions: Few studies have been conducted on models on Burkina Faso agriculture and technology adoption. This study identified agro-ecological zones and others key factors in adoption decision of new maize variety. It is expected that future studies will include these factors as some of the explanatory variables in adoption models.
DOI 10.1186/s40066-015-0035-3
Keywords: Zea mays; Farmers’ preferences; Constraints; Agro-ecological zones; Burkina Faso